ASSOCIATION OF Β-LACTOGLOBULIN PROTEIN ISOFORMS WITH MILK CONSTITUENTS IN GOAT BREEDS - A. Mahmood; M. Jamy; M. Saqlain; P. A. Shaiq; S. M. S. Naqvi; G. K. Raja (Journal of Animal and Plant Sciences, 2016)
The composition of milk and its dairy products is strongly influenced by the polymorphic milk proteins especially β-Lactoglubulin (β-LG). Polymorphism of β-LG has been explored in goats due to the unique nutritional value of milk. In order to explore dairy potential of local Beetal and Daera Din Panah (DDP) goats, we aimed to identify β-LG protein isoforms and their association with milk yield and composition. Whey and casein proteins were isolated from raw skim milk by acid precipitation method. Protein and fat contents were estimated through established methods. Polymorphism in β-LG protein was identified through SDS-PAGE. Daily milk yield and total milk fat contents were significantly elevated in Beetal goat. Three β-LG protein isoforms were identified with genotypes; AA, AB and BB. Frequency of A allele was significantly higher in both goat breeds (p=0.0023 and 0.0001) while heterozygous AB genotype was the most prevalent one. In both goat breeds, all three β-LG protein isoforms lacked association with milk yield and composition. Polymorphism exists in β-LG milk protein in Beetal and DDP Pakistani goats with A allele being the dominant one. The β-LG proteins isoforms lacked association with milk yield and its composition.
Keywords: Polymorphism; Milk; Proteins; Dairy; Genetics